The Bordetella pertussis type III secretion system tip complex protein Bsp22 is not a protective antigen and fails to elicit serum antibody responses during infection of humans and mice - Villarino Romero, Rodrigo; Bibova, Ilona; Cerny, Ondrej; Vecerek, Branislav; Wald, Tomas; Benada, Oldrich; Zavadilova, Jana; Osicka, Radim; Sebo, Peter (Infection and immunity, 2013)
The type III secretion system (T3SS) of pathogenic bordetellae employs a self-associating tip complex protein Bsp22. This protein is immunogenic during infections by Bordetella bronchiseptica and could be used as a protective antigen to immunize mice against B. bronchiseptica challenge. Since low-passage clinical isolates of the human pathogen Bordetella pertussis produce a highly homologous Bsp22 protein (97% homology), we examined its vaccine and diagnostic potential. No Bsp22-specific antibodies were, however, detected in serum samples from 36 patients with clinically and serologically confirmed whooping cough disease (pertussis syndrome). Moreover, although the induction of Bsp22 secretion by the laboratory-adapted 18323 strain in the course of mice lung infection was observed, the B. pertussis 18323-infected mice did not mount any detectable serum antibody response against Bsp22. Furthermore, immunization with recombinant Bsp22 protein yielded induction of high Bsp22-specific serum antibody titers but did not protect mice against an intranasal challenge with B. pertussis 18323. Unlike for B. bronchiseptica, hence, the Bsp22 protein is nonimmunogenic, and/or the serum antibody response to it is suppressed, during B. pertussis infections of humans and mice.
Keywords: Whooping Cough; Bacterial Proteins; myši inbrední BALB C; ELISA; Mice, Inbred BALB C; antigeny bakteriální; Bordetella pertussis; Enzyme-Linked Immunosorbent Assay; Animals; lidé; Humans; zvířata; tvorba protilátek; bakteriální proteiny; myši; protilátky bakteriální; infekce bakteriemi rodu Bordetella; Antigens, Bacterial; Antibody Formation; pertuse; Mice; Bordetella Infections; Antibodies, Bacterial